VOLUNTEERS HELP BRIDGE THE LANGUAGE GAP FOR DEFECTORS. - Kim Hak-Soon (Koreana)
The article presents information regarding the increasing language gap between the people from North Korea and South Korea. It further gives details about the work of English-speaking volunteers to bridge the language gap and teaching the people of South Korea to decrease the usage of slang and increase their English proficiency. It also gives the details about the program undertaken by TNKR Global Education Center, a non-profit facility helping the North Korean people with English speaking.